Impact of Cerebellar Injury on Neurodevelopmental Outcomes in Preterm Infants With Cerebral Palsy. (28th April 2023) - Kim, Yoo Jinie; Kim, Ee-Kyung; Cheon, Jung-Eun; Song, Huijin; Bang, Moon Suk; Shin, Hyung-Ik; Shin, Seung Han; Kim, Han-Suk
Abstract : Objective: We aimed to analyze brain imaging findings and neurodevelopmental outcomes of preterm infants diagnosed with cerebral palsy. Design: Brain magnetic resonance imaging of preterm infants born between 23 and 32 wks' gestation and diagnosed with cerebral palsy at 2 yrs of corrected age were evaluated. Brain lesions were categorized as periventricular leukomalacia, intraventricular hemorrhage, and cerebellar hemorrhage and graded by the severity. Neurodevelopmental outcomes were assessed using the Bayley Scales of Infant and Toddler Development, Third Edition, at 18–24 mos corrected age, and the Korean Ages and Stages Questionnaire at 18 and 24 mos of corrected age. Results: Cerebral palsy was found in 38 children (6.1%) among 618 survivors. Cerebellar injury of high-grade cerebellar hemorrhage and/or atrophy accounted for 25%. Among patients with supratentorial lesions, those having cerebellar injury showed significantly lower scores on each Korean Ages and Stages Questionnaire domain except gross motor than patients without cerebellar injury. They also revealed a high proportion of patients below the cutoff value of Korean Ages and Stages Questionnaire in language, fine motor, and problem-solving domains ( P < 0.05) and lower Bayley Scales of Infant and Toddler Development, Third Edition, language composite scores ( P = 0.038). Conclusions: Poor neurodevelopmental outcomes other than motor function were associated with cerebellar injury. Evaluation of the cerebellum may help predict functional outcomes of patients with cerebral palsy.